2017
DOI: 10.1016/j.tibtech.2017.03.015
|View full text |Cite
|
Sign up to set email alerts
|

How Does Membrane Oxidation Affect Cell Delivery and Cell Killing?

Abstract: The biophysical properties of cellular membranes intimately influence the delivery of cargoes into cells by cell-penetrating peptides and the bactericidal activity of antimicrobial peptides. We discuss how lipid oxidation creates important chemical and biophysical changes in membranes and hypothesize about the observed synergy between oxidized membranes and membrane-active peptides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…However, based on the observed synergy cases, we assume that membranolytic activity of AMPs plays a certain role in the realization of synergistic interaction. We could also hypothesize, that wide-scale oxidative effects provided by silver compounds can contribute to this outcome, as it has been reported that oxidation of membrane lipids potentiated bactericidal activity of membranoactive AMPs (Libardo et al, 2017).…”
Section: Discussionmentioning
confidence: 89%
“…However, based on the observed synergy cases, we assume that membranolytic activity of AMPs plays a certain role in the realization of synergistic interaction. We could also hypothesize, that wide-scale oxidative effects provided by silver compounds can contribute to this outcome, as it has been reported that oxidation of membrane lipids potentiated bactericidal activity of membranoactive AMPs (Libardo et al, 2017).…”
Section: Discussionmentioning
confidence: 89%
“…As far as the biological realm is concerned, our results anticipate a strong influence of hydroperoxidation on the interaction of biomembranes with membrane proteins and with membrane-active biomolecules. [46] Indeed, while enrichment of the head region by -OOH groups will likely enhance the affinity of charged species with the membrane, an increased polarity of the inner membrane is expected to facilitate membrane crossing by species such as cell penetrating peptides.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases an increased activity by a Cu-ATCUN moiety in AMPs was observed for AMPs proceeding through different mechanisms, suggesting a role for Cu-ATCUN motif not restricted to a single antimicrobial mechanism. It is generally explained by promoting oxidative stress [8,15,[21][22][23]25], whether at the membrane (lipid oxidation) or inside the cell, and or via nucleic acid cleavage [8,20,22,26,27]. Noteworthy, it has been suggested that this nucleic acid cleavage by Cu-ATCUN complexes occurs through an oxidative mechanism [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%